Padre Vieira, o homem e o discurso : uma leitura do Sermão do bom ladrão e do Sermão de Santo Antônio aos peixes - Linhares, Esdras Mendes (2007)
Brazilian literary and cultural roots are actually Portuguese since Brazil has a historical, cultural and social relationship with Portugal owing to colonialism. These affinities enhance the importance of studying the literary works of Portuguese authors, especially those closest to Brazilian literature. This is the case of Padre Antonio Vieira known as the orator of the Old and New World. So that the importance of Vieira in Brazilian literature may be evaluated, "The Sermon of the Good Thief" (1998) and "The Sermon of St. Anthony to Fish" (1998) are read critically. The two sermons were chosen for their dense theological contents and for the manner Vieira applies these principles to the problems of contemporary society. The relationship of Vieira's discourse to classical discourse and to the society of his times and his stance with regard to the modus operandi of the institutions of his times have been the factors examined within the chosen corpus. Jauss's Aesthetics of Reception Theory (1985) and Candido's Sociological Critique (1994) underpin current analysis. A bibliographical research has been undertaken so that Vieira's literary work may be placed within its historical, social and ideological context. Classical discourse, comprising its birth, development and its main authors, is investigated so that the classical elements in Vieira's discourse could be assessed for a better understanding of the impact of his eloquence within contemporary society. Modern discourse is further studied through Jauss's aesthetics of reception that highlights the past and present reader's importance in the construction of the literary work's meaning. Candido's "sociological critique" contributes towards this interpretation by establishing the author's relationship with contemporary society. The latter is undertaken through an analysis of society's influence in his writings and through an investigation to see to what extent his ideas have influenced contemporary society and their worth in current society. Context study aims at understanding the author in his own environment and the circumstances in which the literary work was executed. Conclusions are thus applied to the analysis of the literary corpus so that the hypotheses stated at the start may be proved. It is expected that certain aspects of Vieira's ideology will show the progressive stance of the sacred orator.